THU0762-HPR Online consultation for chinese patients with rheumatic diseases based on smart system of disease management (SSDM) mobile tools: a study of medical economics. (15th June 2017) - Xiao, F; Guo, Z; Zhang, Z; Min, W; Tang, Y; Duan, X; Mo, L; Wu, H; Xu, X; Zhao, Y; Jiang, F; Xiao, H; et al.
Abstract : Background: China doesn't have efficient primary medical care and referral system. Patients can choose any hospitals or any doctors they like to seek medical care. As a result, most patients with rheumatic diseases rushed to a few large cities. Survey shows that more than 40% of the rheumatic disease patients are unnecessary to go to hospital and they only need advices from specialist. Smart System of Disease Management (SSDM) is a series of applications for chronic diseases management, which develop the interaction between doctors and patients. Our previous study showed that rheumatoid arthritis (RA) patients can master the SSDM and perform self-management after training, including disease activity score with 28 joints (DAS28) and health assessment questionnaire (HAQ) evaluations, as well as medication and lab test data entries. Objectives: To evaluate the feasibility and benefit of the medical economics of online consultation based on SSDM by rheumatologist. Methods: The rheumatologists implemented the education and training programs on patients in using SSDM and assist the patients in downloading SSDM mobile application. The SSDM includes doctors' and patients' applications. After data entry, patients can synchronize data to their authorized doctor. On the basis of these data, the rheumatologists can accept the request from their follow-up patients through SSDM and practice consultation in the form of text or telephone call. Results: From February 2015 to January 2017, 333 rheumatologists supplied 3, 119 patients (RA 46%, systemic lupus erythematosus 22%, ankylosing spondylitis 12%, Gout 11%, osteoarthritis 4%, other rheumatic diseases 5%) with 136 times free and 3, 556 paid consultations. Paid consulting included 3, 537 times text Q&A and 19 telephone consultations. The consulting fee ranged from RMB 10 to 500 yuan (EUR: RMB =1: 7.33) each in average of 121.3±55.19 yuan, which rate match the registration fee in hospital. The total collection of fee for consultations was 399, 320 yuan RMB. 35.9% patients receiving online consultation lived in different city with the rheumatologists. If patients seek medical in hospital, in addition to the registration fees and medical expenses, the mean cost of transportation, accommodation, meals and lost wages was 552.68±477.51 (200 - 2, 800) yuan. The total of cost for all patients would have been 2, 509, 920 yuan RMB, which is 6.29 times compare with the cost of online. Through the SSDM system for online consultations, patients can save 84.09% of the cost. Survey shows all patients were satisfied and 60.28% of them were "very satisfied" with the consultations. Conclusions: Using SSDM system to obtain online consultation, Chinese patients with rheumatic disease can enjoy reduced cost with high satisfaction. In the era lack of primary care system in China, SSDM may serve a complimentary platform to control medical care cost, as well as relieve the tensions between health care professionals and patients. Disclosure of Interest: None declared